Comparative effectiveness of transurethral resection of bladder tumors and office fulguration for recurrent bladder tumors. (March 2014) - Karakiewicz, Pierre I; Sun, Maxine; Azizi, Mounsif
Evaluation of: Park DS, Hwang JH, Gong IH et al. An analysis of the efficacy, safety, and cost–effectiveness of fulguration under local anesthesia for small-sized recurrent masses: a comparative analysis of transurethral resection of bladder tumors in a matched cohort. J. Endourol. 27(10), 1240–1244 (2013). At initial diagnosis, most bladder tumors are nonmuscle invasive. Some will recur after initial resection and will require transurethral resections of the bladder tumor. Fulguration under local anesthesia represents an alternative. This option is assessed in the article of Park et al. with respect to efficacy, safety and cost–effectiveness in patients with small-sized recurrent bladder tumors. The authors suggest that fulguration is safe and efficacious without compromising oncological outcomes in selected patients relative to formal transurethral resections of bladder tumor.